Keefektifan Pendidikan Kesehatan Dengan Metode Demonstrasi Terhadap Keterampilan Ibu Dalam Pijat Bayi - Mia Rita Sari; Madinah (STIKes Payung Negeri Pekanbaru, 2021)
Baby massage is one form of physiotherapy that positively affects the growth process of toddlers in addition to supplementary feeding. There are still many parents who do not understand about baby massage, some think baby massage is done only on sick babies and by herbalists or medical personnel who master baby massage. Due to the lack of knowledge possessed by the mother, health workers can provide health education about baby massage by demonstration method because one's skills can be honed through demonstration method. This study aims to find out the effectiveness of health education by demonstration method of maternal skills in baby massage in Posyandu Serai Wangi Working Area Pustu Pekan Arba Tembilahan Kota. The design of the study was pre-experimental, with a pre test and post test approach without a control group, a sample of 21 mothers. Sampling using simple random sampling technique. Data collection through interviews and cheklist sheets. Data analysis using t-test statistics. The results of the study obtained the average skills of mothers in performing baby massage before and after health education with demonstration methods of 54.67 and 70.81. Based on the results of statistical tests of health education with effective demonstration methods to improve the mother's skills in performing baby massage (0.000 < 0.05) so that it is expected that the mother is able to perform baby massage independently